English learners with dyslexia benefit from English dyslexia intervention: an observational study of routine intervention practices - Middleton, Anna E.; Davila, Marcela; Frierson, Sheryl L. (Frontiers in Education, 2024)
IntroductionLearning to read when the language of the curriculum differs from one’s home language can pose unique challenges. For example, compared to the language spoken at home, the learner may be less familiar with the sound structure and have relatively limited word knowledge in the language of instruction. In the United States, English is the primary language of reading instruction for students who are English Proficient (EP) and for English Learners (EL). Current evidence indicates that for both EP and EL students, code-based competencies and meaning-based skills are important for learning to read. English-language reading interventions have been shown to be beneficial for EPs and ELs with reading problems, though it is not clear if this is also true when the reading problem is a reading disorder like dyslexia.MethodsThe current study addresses this question by comparing EL and EP student’s reading profile at baseline and changes over time in response to evidence-based English Language Dyslexia Instruction (ELDI) in public schools. One-hundred eighty-six students with dyslexia were followed over the course of two academic years. Assessments measured code and meaning-based reading skills. Multivariate profile analysis and linear mixed effects modeling were conducted to compare baseline reading profiles as well as growth in targeted skills over time.ResultsFindings reveal similar patterns of reading profiles across EL and EP groups, with more severe baseline deficits emerging for ELs. Groups performed equivalently on target reading skills after two years of intensive multi-componential reading intervention.ConclusionFindings confirm and extend previous research, suggesting ELs with Dyslexia can be identified and successfully served through routine practices, including ELDI.